2015
DOI: 10.1007/s00417-015-3214-9
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state multifocal visual evoked potential (ssmfVEP) using dartboard stimulation as a possible tool for objective visual field assessment

Abstract: Our results in normal subjects indicate that reliable mfVEP responses can be achieved by steady-state stimulation using a conventional dartboard stimulator and multi-channel electrode device. The ssmfVEP may be useful for objective visual field assessment as spectrum analysis can be used for automated evaluation of responses. The optimal reversal frequency is 8.6 Hz. Alpha waves have only a minor influence on the analysis. Future studies must include comparisons with conventional mfVEP and psychophysical visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…For all four arrays, the stimulus frequency resulting in the maximal VEP response was between 10 and12 Hz. This is in agreement with previous studies 4,32,33. Furthermore, the amplitudes were similar to those found previously in experiments using conventional multifocal stimuli34 and with the steady-state multifocal VEP 4.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…For all four arrays, the stimulus frequency resulting in the maximal VEP response was between 10 and12 Hz. This is in agreement with previous studies 4,32,33. Furthermore, the amplitudes were similar to those found previously in experiments using conventional multifocal stimuli34 and with the steady-state multifocal VEP 4.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies 4,32,33. Furthermore, the amplitudes were similar to those found previously in experiments using conventional multifocal stimuli34 and with the steady-state multifocal VEP 4. However, in contrast to earlier studies where the amplitudes were largest in the lower stimulus fields,20,35,36 we found the largest amplitudes in the upper-right quadrant.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations